Do Gender Differences Influence the Quality of Life of People Living with HIV/AIDS? - Deshmukh, Namita N; Deshmukh, Jyotsna S; Borkar, Avinash M; Ughade, Suresh N; Lone, Deepak K; Bhatkule, Prakash R; Khamgaonkar, Mohan B (National Journal of Community Medicine, 2014)
Introduction: Given the longevity achievable with the current Antiretroviral Therapy (ART) for People Living with HIV/AIDS, quality of life (QOL) has emerged as a significant measure of health outcome. Also, younger age, higher socioeconomic status and employment have been associated with improvement in QOL. Hence, the present study has made an attempt to examine gender differences in QOL of People living with HIV/AIDS (PLWHA). Material and methods: It was a cross sectional study carried out on 754 HIV positive patients attending the anti-retroviral treatment clinic of the IGGMC, Nagpur from March 2010 to June 2011 .Socio-demographic characteristics of the patients were studied and quality of life was assessed by WHOQOL-HIVBREF scale. Chi-square test, z-test and multiple logistic regressions were used for analysis. Results: Out of 754 study subjects, 461(61.1%) were male and 293(38.9%) were female patients. It was observed that92.2% males and 80.2%females were literate, 50.8%females were widowed, divorced or separated and only 41.6% females were employed. Females had poor nutritional status as indicated by haemoglobin levels (9.3 gm% ± 1.33) and Body Mass Indices (19.3 Kg/m2 ± 2.95). They had lower total QOL score than male patients. Women had significantly lower scores in social relationships (11.5±3.55) and environmental domains (10.6 ± 2.19), (p<0.001) of Quality of Life. Conclusions: Women had a poor quality of life as compared to men. Poor living conditions, lack of social support, illiteracy are the factors along with the fact of being HIV positive which could be incriminated towards these findings.